Studies on the inhibition of highly purified calf thymus 8S and 7.3S DNA polymerase alpha by aphidicolin. - Holmes, A M (1981)
On activated DNA aphidicolin competitively inhibits the incorporation of dCMP by both calf thymus DNA polymerase alpha A2 and C enzymes and inhibits the incorporation of the other three deoxynucleoside monophosphates apparently non-competitively. However, aphidicolin does not inhibit the incorporation of dAMP into poly(dT) . oligo(A)10 nor does it inhibit the incorporation of dGMP into poly(dC) . oligo(dG)10, but, it does competitively inhibit the incorporation of dTMP into poly(dA) . oligo(dT)10.